Systematic analysis of MCM3 in pediatric medulloblastoma via multi-omics analysis - Cao, Liangliang; Zhao, Yang; Liang, Zhuangzhuang; Yang, Jian; Wang, Jiajia; Tian, Shuaiwei; Wang, Qinhua; Wang, Baocheng; Zhao, Heng; Jiang, Feng; Ma, Jie (Frontiers in Molecular Biosciences, 2022)
MCM3, as one member of minichromosome maintenance proteins family, which are DNA-dependent ATPases that binds to replication origins and licenses them to support a single round of DNA replication, has been reported disfunction in most cancers. To systematically elucidate the mechanisms involved in medulloblastoma(MB) affected by aberrant MCM3 expression and evaluate its clinical significance, we analyzed the multi-omics data from GEO database and validated them with our cohort data. First, we showed the upregulation of MCM3 in MB and revealed MCM3 might take effect via the DNA replication at bulk RNA sequence and single cell RNA sequence level. Then we found the dysregulation of MCM3 might result from abnormal methylation of MCM3. Moreover, we discovered MCM3 correlated immune components, like fibroblast, neutrophiles, were associated with over survival in MB subtypes, and that MCM3 might affect varied biological processed like apoptosis, autophagy and ferroptosis. Furthermore, we found that MCM3 expression was correlated with IC50 of cisplatin and etoposide, and the nomogram based on MCM3 related genes showed reliable prediction ability on the 1 and 5-year survival. Overall, our study demonstrated that the aberrant expression of MCM3 might affect extensive processes, and could serve as a valuable biomarker with clinical significance.